1992
DOI: 10.1007/bf00300790
|View full text |Cite
|
Sign up to set email alerts
|

The child with a mass on its head: diagnostic and surgical strategies

Abstract: A series of 65 pediatric patients with scalp or calvarial masses is reported on. The majority of children presented with a disfiguring or painful mass on the head. Clinical findings suggested the correct diagnosis in 39/65 cases, skull radiographs in 46/65, and CT in 49/65. Taking the combined results of clinical and radiological studies, 54/65 of the lesions were accurately diagnosed. Tumor excision was curative in 43 of 48 patients who were operated on. Most scalp and calvarial neoplasms were benign; only 5/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 18 publications
1
36
1
1
Order By: Relevance
“…This has been reported to comprise 7-10.8% of scalp masses in children [16,20], but we observed that it was the most common type of scalp lesion in our study, occurring in 16 of 75 cases (20.8%). Ninety percent of this condition occurs in children aged 5-15 patients as a tender mass [2,16,19,22]. The site of occurrence is irrespective of cranial sutures and usually does not penetrate the dura [20].…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…This has been reported to comprise 7-10.8% of scalp masses in children [16,20], but we observed that it was the most common type of scalp lesion in our study, occurring in 16 of 75 cases (20.8%). Ninety percent of this condition occurs in children aged 5-15 patients as a tender mass [2,16,19,22]. The site of occurrence is irrespective of cranial sutures and usually does not penetrate the dura [20].…”
Section: Discussioncontrasting
confidence: 48%
“…Late recurrent disease has been reported 10 years after initial therapy, and therefore, long-term follow-up is recommended. Solitary LCH lesions of the skull show a low incidence of recurrence (0-1.5%), but this may be as high as 31% in other reports [16,19]. We experienced one case (1 of 16) of recurrence in this study.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations